Gallic acid regulates primary root elongation via modulating auxin transport and signal transduction - Xu, Zilian; Yang, Bing; Fan, Jing; Yuan, Qiushi; He, Fu; Liang, Hongwei; Chen, Faju; Liu, Wen (Frontiers in Plant Science, 2024)
Gallic acid is an important secondary metabolite in plants, with great value in medicine, food, and chemical industry. However, whether and how this widely existing natural polyphenolic compound affects the growth and development of plants themselves remains elusive. In this study, we revealed that exogenous application of gallic acid has a dual effect on the elongation of primary root in Arabidopsis. While lower concentrations of gallic acid slightly stimulate primary root growth, excessive gallic acid profoundly reduces primary root length and root meristem size in a dosedependent manner, probably via suppressing cell division in root meristem as indicated by CYCB1;1::GUS. Moreover, as suggested by the DR5::GFP line analysis and confirmed by the LC-MS assay, auxin contents in root tips were dramatically decreased upon excessive gallic acid treatment. Additional application of IAA partially rescued the shortened primary root and root meristem upon excessive gallic acid treatment, suggesting that auxin is required for excessive gallic acid-caused root growth inhibition. Then, we further revealed that excessive gallic acid down-regulated the expression of auxin transporters PIN1, PIN2, PIN3, and PIN7, and triple mutant pin1pin3pin7 exhibited a reduced sensitivity to gallic acid treatment. Meanwhile, excessive gallic acid decreased the degradation of AXR3/IAA17 protein as revealed by HS::AXR3NT-GUS reporter line. Auxin signaling mutant tir1afb2afb3 and axr3-3 were also less sensitive to excessive gallic acid treatment in terms of primary root length and root meristem size. Taken together, these findings suggested that excessive gallic acid inhibits primary root growth by modulating auxin transport and signaling in Arabidopsis.